ESTATÍSTICA: UMA PROPOSTA DE FORMAÇÃO CONTINUADA PARA PROFESSORES DE MATEMÁTICA DO ENSINO FUNDAMENTAL E MÉDIO - Dessbesel, Renata da Silva (2013)
This study aimed to analyze the statistics teaching by elementary and secondary teachers in public schools in Cruz Alta and evaluate workshops for continuing education to mathematics teachers, approaching statistics contents and using support material. Characterized as a research field, the investigation has qualitative and quantitative nature, the participants are teachers from 16 public schools in the city of Cruz Alta. From a review of official documents related to Statistics Education and dissertations that have worked with this theme, a questionnaire was applied to 58 teachers, whose responses are presented and discussed. In order to supplement the survey responses, interviews were conducted with five teachers and also continuing education workshops were realized with teachers who work in public schools in the elementary and high school in Cruz Alta. From the data collected, it was found that among the contents of statistics in the elementary school, organizing data in a table and the construction of line graphs and bar are addressed more frequently. In high school, graphical representation of data and measures of central tendency (arithmetic mean, median and mode) are the contents more elaborated. In analyzing the responses to the questionnaires and interviews, it was realized that the use of computers as teaching resource was cited, in particular the use of the Excel spreadsheet. It was also noted that teachers want to participate in continuing education courses, since these contemplate their needs and are practical ones. As a product of this dissertation work, we designed a study guide, available on CD-ROM and on the website of the Professional Master Course in Physics and Mathematics Teaching, from UNIFRA.